1998
DOI: 10.1183/09031936.98.12051118
|View full text |Cite|
|
Sign up to set email alerts
|

Tidal expired airflow patterns in adults with airway obstruction

Abstract: Earlier studies have shown that time and flow indices derived from tidal expiratory flow patterns can be used to distinguish the severity of airway obstruction. This study was designed to address two aspects of tidal expiratory flow patterns: 1) how do expiratory flow patterns differ between subjects with normal and obstructed airways; and 2) can a sensitive index of airway obstruction be derived from these pattern differences? Tidal expiratory flow patterns from 66 adult subjects with varying degrees of airwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 13 publications
3
24
0
Order By: Relevance
“…On the other hand, assessment of the spontaneous expiratory flow-volume (SEFV) curve has been reported as a method to evaluate the severity of airway obstruction, which has the advantage that it is easily measured via spirometry during quiet breathing. [3][4][5][6][7][8][9][10] Shortening of the time to reach the peak expiratory flow 3 and the slope of the late SEFV curve, 4 which can be obtained from the SEFV curve, has been reported to be related to airway obstruction. Moreover, a method to assess the pattern of the SEFV curve has been reported, and concavity of the SEFV curve has been found to be related to expiratory flow limitation.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, assessment of the spontaneous expiratory flow-volume (SEFV) curve has been reported as a method to evaluate the severity of airway obstruction, which has the advantage that it is easily measured via spirometry during quiet breathing. [3][4][5][6][7][8][9][10] Shortening of the time to reach the peak expiratory flow 3 and the slope of the late SEFV curve, 4 which can be obtained from the SEFV curve, has been reported to be related to airway obstruction. Moreover, a method to assess the pattern of the SEFV curve has been reported, and concavity of the SEFV curve has been found to be related to expiratory flow limitation.…”
Section: Introductionmentioning
confidence: 99%
“…MORRIS et al [1] examined the latter part of the tidal expiratory flow pattern in patients with varying degrees of airflow obstruction and found that the expiratory time constant correlated positively with standard measures of airflow obstruction. WILLIAMS et al [2] also showed that a shape index related to the rate of decay of post-maximal expiratory flow correlated strongly with airflow obstruction, as determined by conventional methods. These studies suggest that a simple, noninvasive procedure may be used to derive an important physiological parameter that is not normally so easily obtained.…”
Section: Jht Batesmentioning
confidence: 95%
“…The results of MORRIS et al [1] and WILLIAMS et al [2] are, therefore, interesting from a clinical perspective be-cause they suggest that the severity of airflow obstruction, a parameter of key concern to the respiratory specialist, may be derived easily and noninvasively, namely from airflow measurements at the mouth. The physiological basis of this approach is not difficult to appreciate.…”
Section: Jht Batesmentioning
confidence: 99%
See 2 more Smart Citations